Concept of Independent Character Based on Pathfinder (Cross Case Study) - Samsul Hidayat; Yus Mochamad Cholily; Khozin Khozin; Afiful Ikhwan (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
This research aims to analyze the concept of independent character by looking at it from a scouting perspective. This research explains how scouting and Hisbul Wathan explain the idea of independent character. A qualitative approach was used to describe this study by taking a cross-case study type with the study locus in two different institutions that implement the character of independence through scouting education. Data collection techniques through interviews, observation, and documentation. Data analysis techniques use data condensation, data presentation, and conclusions. This research reveals that the concept of independent character based on scouting grows together with the education and routine training of Hizbul Wathan and Scouts. The thoughts of KH. Ahmad Dahlan inspired the idea of independence in Hizbul Wathan. Ahmad Dahlan is a responsible, skilled, independent and disciplined human being. The concept of independence in Scouting follows up on the Minister of Education and Culture of the Republic of Indonesia Regulation Number 23 of 2015 concerning the Development of Character. The limitation of this research is that it focuses on scouting to explain the concept of independence. Meanwhile, originality lies in the scouting movement as an independent character education concept.